2020
DOI: 10.1158/1078-0432.ccr-19-1486
|View full text |Cite
|
Sign up to set email alerts
|

Colony-Stimulating Factor 1 Receptor (CSF1R) Activates AKT/mTOR Signaling and Promotes T-Cell Lymphoma Viability

Abstract: Purpose: Peripheral T-cell lymphomas are clinically aggressive and usually fatal, as few complete or durable remissions are achieved with currently available therapies. Recent evidence supports a critical role for lymphoma-associated macrophages during T-cell lymphoma progression, but the specific signals involved in the cross-talk between malignant T cells and their microenvironment are poorly understood. Colony-stimulator factor 1 receptor (CSF1R, CD115) is required for the homeostatic survival of tissue-res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 78 publications
0
37
0
Order By: Relevance
“…As downstream effectors of TAMs, M2-induced cytokine IL-10, as well as immunosuppressive factors B7-H4 and CSF1R, were increased correspondingly, which may inhibit the cytotoxic activity of tumor-associated antigen-specific T cells and promote lymphoma cell evasion. 44 46 Our data demonstrated that the FBXW7-NOTCH-CCL2/CSF1 axis as an important mechanism of tumor progression provoked by TAMs in DLBCL. Considering that the NOTCH inhibitor has an off-target effect and is toxic if applied systemically, designing a more effective way to target CCL2/CSF1 can be a feasible immune intervention for DLBCL treatment.…”
Section: Discussionmentioning
confidence: 70%
“…As downstream effectors of TAMs, M2-induced cytokine IL-10, as well as immunosuppressive factors B7-H4 and CSF1R, were increased correspondingly, which may inhibit the cytotoxic activity of tumor-associated antigen-specific T cells and promote lymphoma cell evasion. 44 46 Our data demonstrated that the FBXW7-NOTCH-CCL2/CSF1 axis as an important mechanism of tumor progression provoked by TAMs in DLBCL. Considering that the NOTCH inhibitor has an off-target effect and is toxic if applied systemically, designing a more effective way to target CCL2/CSF1 can be a feasible immune intervention for DLBCL treatment.…”
Section: Discussionmentioning
confidence: 70%
“…CSF1R signaling is associated with significant changes in gene expression and the phosphoproteome, which indicates that the PI3K/AKT/mTOR axis promotes CSF1R-mediated T-cell lymphoma growth. 16 The transcription factor FOXO1 is downstream of PI3K/AKT in macrophages, 17 and it facilitates M2 polarization. 12 Therefore we detected the effects of CSF1 derived from HCVECs on the PI3K/AKT/FOXO1 axis in human macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…CSF1R has a role in regulating the homeostatic survival of the tumor-associated macrophages (TAMs). TAMs are relevant because they promote tumorigenesis of many types of cancer, including non-Hodgkin lymphomas [23,[35][36][37][38]. Therefore, CSF1R is a potentially relevant oncological target.…”
Section: Discussionmentioning
confidence: 99%